Your answer is c.
Step-by-step explanation: Let’s say P is worth 1: 9 times 1 equals 9: 3 times 1 equals 3: 9 - 3 = 6/ 6 + 2 equals 8. Now this is C: 6 times 1 equals 6/ 6+ 2 = 8
What is this a joke or what if so mark me brainlieast
Answer:
Synthetic division is another way to divide a polynomial by the binomial x - c , where c is a constant.
Step 1: Set up the synthetic division. ...
Step 2: Bring down the leading coefficient to the bottom row.
Step 3: Multiply c by the value just written on the bottom row. ...
Step 4: Add the column created in step 3.
Step-by-step explanation:
hope this helps you :)
Complete the square:
<span>y = 3x^2 - 12x + 4 </span>
<span>y = 3(x^2 - 4x) + 4 </span>
<span>y = 3(x^2 - 4x + 4 - 4) + 4 </span>
<span>y = 3(x^2 - 4x + 4) - 12 + 4 </span>
<span>y = 3(x - 2)^2 - 8</span>
Answer:
Yes.
Step-by-step explanation:
Set the equations equal to each other to determine their equality.
-4[3(x - 7)] = 6(14 - 2x)
Distribute the 3 and the 6 into their respective parenthesis.
-4[3x - 21] = 84 - 12x
Distribute the -4 into the brackets.
-12x + 84
Rearrange the equations.
84 - 12x = 84 - 12x
Since the equations come out to be the same thing on both sides so that any value satisfies it, the equations are equivalent.